Secukinumab improves the quality‐of‐life of family members and partners of people with psoriasis: Family Dermatology Life Quality Index (FDLQI) results from a randomised open‐label study (SIGNATURE). Issue 3 (29th June 2022) - Finlay, A. Y.; Barker, J. N.; Burden, A. D.; Griffiths, C. E. M.; Kirby, B.; Goodman, M. L.; Neill, C.; Warren, R. B.
Abstract: Background: The Family Dermatology Life Quality Index (FDLQI) was developed to meet a need for a dermatology‐specific family member/partner quality‐of‐life (QoL) measure. This paper focuses on the analysis and interpretation of FDLQI data (used as an exploratory outcome) collected in the SIGNATURE study. Objectives: To measure the impact of secukinumab therapy for moderate to severe plaque psoriasis on the QoL of family members/partners of patients. Methods: Randomised, open‐label, non‐comparator study in 53 dermatology centres in the UK and Republic of Ireland. Patients received secukinumab 300 or 150 mg subcutaneously weekly for 4 weeks, then 4‐weekly. FDLQI Results: Family members of PASI 75 responders and non‐responders showed improved FDLQI compared to baseline, greater for responders. There was a high level of correlation between FDLQI and Dermatology Life Quality Index (DLQI) scores and positive correlations across all mapped FDLQI and DLQI questions, and a close association between the scales at all timepoints. The estimated FDLQI scores were consistently 56% of those obtained for DLQI. There was an improvement for all FDLQI questions at Week 16 with a mean total score change of 8.2. Most family member subjects had an improved score for all FDLQI questions (75%–91%, Week 12, and 77%–91%, Week 16). Family subjects with a corresponding patient visit DLQI score >10 improved for all FDLQI questions at Week 16 (mean total score change of 5.2). Conclusions: Successful therapy for severe psoriasis greatly improved QoL of family members/partners. The FDLQI questionnaire responds well and appropriately to major changes in the disease severity of those affected by plaque psoriasis.